A House Burden Score: Measuring the Workload in Therapeutic Residential Care for Young People. Issue 4 (2nd October 2021) - Ainsworth, Frank; Mastronardi, Paul
ABSTRACT: This article is about using data from the Strengths and Difficulties questionnaire to develop a house burden score as a way of measuring the workload of a therapeutic residential care program. The development of the score ensures that residential placement selection is based on empirical data rather than on the often-used criteria of ' where is there a vacancy?' It may also curb comments by inexperienced staff such as 'our house has the most difficult young people, whereas yours are easy' . The aim of the score is to ensure that a residential program is not overburdened with too many children and young people with complex emotional and behavioral difficulties to the extent that this result is a sub-standard service for all young people.